Study on Seismic Resilience Quantitative Framework of Subway Stations and Resilience Improvement Strategy - Dong, Zhengfang; Li, Chengjie; Wen, Sen; Zhai, Pengfei; Kang, Shuai (Frontiers in Earth Science, 2022)
Improving the seismic resilience of urban underground structures is among the hot topics concerning disaster prevention and the mitigation engineering of underground structures; however, there is still a lack of research on the quantitative methods for the seismic resilience of underground structures. Based on the existing research results of seismic resilience in other fields and combined with the actual situation of subway stations, in this paper, a quantitative framework for the seismic resilience of subway stations was proposed. In this quantitative framework, the seismic resilience of subway stations was described from the functional and economic levels, respectively, with two indices. Also, a recovery model and an indirect economic loss calculation method for subway stations were proposed. Based on the proposed framework, the strategy and mechanism of improving seismic resilience were analyzed. Moreover, a finite element model was established to calculate and analyze the effects of the two strategies on enhancing the seismic resilience of subway stations by adding seismic mitigation measures before earthquakes and accelerating restoration after earthquakes. The results showed that the proposed framework is feasible, as both strategies showed to improve the seismic resilience of a subway station; however, the mechanisms are different. After the installation of seismic mitigation measures before an earthquake, the functional recovery capacity of the station increased by 22%–30%, and the economic loss decreased by 43%–75%. After the earthquake, by increasing the number of repair workers, the functional recovery capacity increased by 5%–25%, and the economic losses decreased by 10%–48%.